The effect of light therapy on sleep disorders and psychobehavioral symptoms in patients with Alzheimer’s disease: A meta-analysis - Zang, Lili; Liu, Xiaotong; Li, Yu; Liu, Jiang; Lu, Qiuying; Zhang, Yue; Meng, Qinghui (PLOS ONE, 2023)
Background Although Alzheimer’s disease (AD) mainly affects cognitive function, it is often accompanied by sleep disorders and psychobehavioral symptoms. These symptoms, including depression, agitation, and psychotic symptoms, are prominent hospitalization causes among patients with AD. Currently, relatively more research exists on light therapy for sleep disorders, while those on psychobehavioral symptoms are gradually increasing. However, no consensus exists on these results because of the vulnerability of light therapy to multiple factors, including light intensity and duration. Thus, further research investigating this aspect is warranted. Objective To evaluate the efficacy of light therapy in improving sleep disorders and psychobehavioural symptoms in patients with AD. Methods In this meta-analysis, relevant literature was searched in Embase, the Clinical Trials Registry, Web of Science, PubMed, and the Cochrane Library up to December 2022. Furthermore, a fixed-effects model was used for data analysis. Results Fifteen randomized controlled trials involving 598 patients with AD were included. In the case of sleep disorders, our meta-analysis revealed that light therapy significantly improved sleep efficiency (MD = −2.42, 95% CI = −3.37 to −1.48, p < 0.00001), increased interdaily stability (MD = −0.04, 95% CI = −0.05 to −0.03, p < 0.00001), and reduced intradaily variability (MD = −0.07, 95% CI = −0.10 to −0.05, p < 0.00001). With respect to psychotic behavior, light therapy was found to alleviate depression (MD = −2.55, 95% CI = −2.98 to −2.12, p < 0.00001) as well as reduce agitation (MD = −3.97, 95% CI = −5.09 to −2.84, p < 0.00001) and caregiver burden (MD = −3.57, 95% CI = −5.28 to −1.87, p < 0.00001). Conclusion Light therapy leads to significant improvement in sleep and psychobehavioral symptoms and is associated with relatively fewer side effects in patients with AD, indicating its potential as a promising treatment option for AD.